Exploring the Impact of Good Governance and Innovation on Export Earnings, Clean Energy, Remittances, and Zero Carbon Emissions in Sub-Saharan African Countries - Mindia, Piana Monsur; Qamruzzaman, Md; Farzana, Nusrat (International Journal of Energy Economics and Policy, 2024)
The research examines how to export earnings, remittances, good governance, clean energy, innovation, and carbon neutrality are interconnected in Sub-Saharan African countries from 2001 to 2020. By using panel data analysis methods, the study explores the connections between these factors to understand the factors influencing carbon neutrality and their impact on sustainable development in the region. The analysis indicates that export earnings, remittances, and clean energy positively correlate with achieving carbon neutrality. Export earnings drive economic growth and support investments in cleaner technologies and environmental sustainability. Remittances boost household incomes, enabling the adoption of cleaner energy sources. Additionally, using clean energy technologies is linked to lower carbon emissions, emphasizing the need to transition to renewable energy sources for carbon neutrality. Conversely, the findings suggest negative connections between good governance, innovation, and achieving carbon neutrality. Countries with stable governance tend to have lower carbon emissions due to the effective implementation of environmental policies. However, the negative link between innovation and carbon neutrality implies that technological progress can increase emissions without investments in clean energy and sustainable practices. The study also highlights the significance of good governance in enforcing environmental policies. Furthermore, it stresses the need to balance economic growth with environmental sustainability, emphasizing the role of innovation in achieving sustainable development. The study adds to current research by presenting data on the factors influencing carbon neutrality in Sub-Saharan Africa. It highlights the connections between export earnings, remittances, governance, innovation, clean energy, and carbon neutrality, offering vital information for policymakers aiming to encourage sustainable development and address climate change in the area.